Glycolysis and Oxidative Phosphorylation Play Critical Roles in Natural Killer Cell Receptor-Mediated Natural Killer Cell Functions - Wang, Zixi; Guan, Di; Wang, Shu; Chai, Louis Yi Ann; Xu, Shengli; Lam, Kong-Peng (Frontiers in Immunology, 2020)
Natural killer (NK) cells are innate lymphocytes that directly kill tumor and pathogen-infected cells upon activation by cytokines and NK cell receptors (NKRs) without previous sensitization. It is known that cell metabolism affects the differentiation and effector functions of immune cells. For instance, interleukin-2 and interleukin-15 treatment increases glycolysis and oxidative phosphorylation (OXPHOS) in NK cells to support their effector functions. However, little is known about the metabolic reprogramming of human NK cells upon their activation by NKRs. In this study, we investigated the metabolism of NK cells stimulated via NKRs. We found that NK cells upregulated glycolysis and OXPHOS in response to anti-CD16 antibody and NKG2D ligand engagement. Inhibition of either glycolysis or OXPHOS impaired NK cell production of interferon-gamma. Interestingly, inhibition of glycolysis but not OXPHOS decreased NK cell killing and dampened NK cell degranulation and Fas ligand expression, suggesting that glycolysis is more critical for NKR-activated cell cytotoxicity. Thus, our study provides insight into understanding the metabolic requirements underlying different effector functions of human NK cells.